Protein arginine methyltransferases in renal development, injury, repair, and fibrosis - Yu, Jianjun; Yu, Chao; Bayliss, Georgia; Zhuang, Shougang (Frontiers in Pharmacology, 2023)
Protein arginine methyltransferases (PRMTs) methylate a range of histone and non-histone substrates and participate in multiple biological processes by regulating gene transcription and post-translational modifications. To date, most studies on PRMTs have focused on their roles in tumors and in the physiological and pathological conditions of other organs. Emerging evidence indicates that PRMTs are expressed in the kidney and contribute to renal development, injury, repair, and fibrosis. In this review, we summarize the role and the mechanisms of PRMTs in regulating these renal processes and provide a perspective for future clinical applications.